Faktor-Faktor Penyebab Rendahnya Minat Siswa Terhadap Pembelajaran Tari Di SMK Taruna Padang - Sera Malina; Yuliasma Yuliasma (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine and describe the factors causing the low interest of students in learning dance at SMK Taruna Padang. The type of research used is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through observation, interviews and documentation. The steps of analyzing data are collecting data, describing data, identifying data, analyzing data and inferring data. The results showed that student interest in SMK Taruna Padang can be seen from the factors causing students' low interest in learning dance. These factors are student factors, teacher factors and school factors. This means that from the student factor seen from 2 indicators, namely desire and attention, the results of observations from meetings 1 to 4 are that with teacher limitations in the use of learning media, less varied methods and angry teacher attitudes and low desire and attention in learning dance, especially in learning practice. The dislike of students in lessons can be seen that many students are noisy and in and out of class and do not like to follow dance lessons well.